Crop prediction and diversification for Nuevo León, Mexico - Ramírez Gómez, Gustavo Andrés; Gutiérrez Castorena, Edgar Vladimir; Ortíz Solorio, Carlos Alberto; Gutiérrez Castorena, Maria del Carmen (Revista Mexicana de Ciencias Agrícolas, 2020)
The factors involved in the prediction of areas for food production are subject to cultural, socioeconomic variables, water availability and particular characteristics of its management and production. Agriculture as a micro business activity is subject to risks that force to improve predictive mechanisms of climatic and edaphic variables. The main objective is to generate models from various databases and thematic maps at the same observation scale to locate areas with productive potential of 16 crops with economic value in the national and strategic market for the state of Nuevo León. This state was selected for belonging to three physiographic regions with great edaphoclimatic diversity, which requires proven methods both nationally (Ortíz, 2011) and internationally for zoning. Different databases such as aptitude in terms of thermal efficiencies, frost-free period and classification, degradation and water regime of the soils were used. The results show that with the information collected and analyzed, the areas on maps for basic grains, vegetables and fruit can be located and quantified in more than 50% of the state agricultural area and other crops in areas less than 10%. The best agricultural area is located in the central north of the state; however, the determining factor for the growth of the main crops is the frost-free period. It is recommended to grow early varieties of basic grains and vegetables to take advantage of the months with greater efficiencies.
Keywords: classification; crop suitability; soil degradation; thermal efficiency; yield